2018
DOI: 10.1016/j.applanim.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Poker Face: Discrepancies in behaviour and affective states in horses during stressful handling procedures

Abstract: Correct assessment of stress in horses is important for both horse welfare and handler safety during necessary aversive procedures. Handlers depend on behaviour when judging how well an individual is tolerating stressful procedures such as loading or veterinary intervention. However, evidence suggests that behaviour may not accurately reflect affective states in horses. This may be explained by individual

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 26 publications
3
53
1
1
Order By: Relevance
“…wide, from which hung 2m long coloured plastic streamers (Squibb et al, 2018). To complete this test, the subject walked through the frame, causing the streamers to touch the face and body of the subject as they passed through.…”
Section: Handling Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…wide, from which hung 2m long coloured plastic streamers (Squibb et al, 2018). To complete this test, the subject walked through the frame, causing the streamers to touch the face and body of the subject as they passed through.…”
Section: Handling Testsmentioning
confidence: 99%
“…Crossing time began when the first fore-limb bore weight after the ground pole 2m in front of the obstacle. Crossing time ended when the last hind-limb bore weight on the tarpaulin for Test A (Ijichi et al, 2013), or when the tail of the subject had passed through the frame for Test B (Squibb et al, 2018). Horses that did not complete the test were recorded a Crossing Time of 180 seconds.…”
Section: Behaviourmentioning
confidence: 99%
“…The inability of owners to recognise patterns of behaviours of horses that underpin negative emotional states has been explored by [13] and has been confirmed to have major welfare implications. This is complicated further by the potential for individual horses to be more, or less, overt in their behavioural expression of underlying emotions, and for the effect of training to mask any emotional response that would otherwise be present [14]. Likewise, individual horses cope with stress in different ways [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, contrary to our expectations, we did not find any differences in these traits between stereotypic and control horses. Since reactive coping strategies are characterised by freeze responses and unresponsiveness, it might be more difficult to detect fear in these animals (Squibb et al, 2018). Surprisingly, however, we found that a greater proportion of cribbiters reacted to the tactile filaments compared with the control horses suggesting a higher tactile sensitivity, which to our knowledge has never been reported before.…”
Section: Discussioncontrasting
confidence: 62%
“…Indeed, behavioural reactions to fear-induced reactions might be less strongly expressed (e.g. characterized by freeze responses and unresponsiveness) in those individuals compared to proactive ones Squibb et al, 2018).…”
Section: Curiosity/fearfulnessmentioning
confidence: 96%